2022
DOI: 10.1097/md.0000000000031915
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of trunk muscles activity during horseback riding machine exercise in children with spastic cerebral palsy

Abstract: Appropriate trunk muscle activity is needed to perform functional activities in cerebral palsy, this study analyzed the activity of trunk muscles during horseback riding machine exercise in children with spastic cerebral palsy. 10 children with spastic cerebral palsy were participated, the activity of the trunk muscles, including both sides of the rectus abdominis, external oblique, latissimus dorsi, and erector spinae in sitting posture and during horseback riding machine exercise were evaluated using a surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Items in both tests require lateral pelvic lifting, which involves activation and control of trunk, pelvic, and abdominal muscles that contribute to core stability [80]. Although most studies to date have measured flexor and extensor muscle activity [81][82][83][84][85], one study reported high magnitudes of muscle activity from the internal oblique abdominus in older non-riders [82] and another between novice and advanced jockeys [86], highlighting the involvement of other core stabilizers. Greater mediolateral amplitude and velocity of the center of pressure have been measured during riding in a group of cerebral palsy participants with five years of therapeutic riding experience compared to controls, also illustrating a deficit in mediolateral trunk control due to impairment [87].…”
Section: The Relationship Between Impairment and Performancementioning
confidence: 99%
“…Items in both tests require lateral pelvic lifting, which involves activation and control of trunk, pelvic, and abdominal muscles that contribute to core stability [80]. Although most studies to date have measured flexor and extensor muscle activity [81][82][83][84][85], one study reported high magnitudes of muscle activity from the internal oblique abdominus in older non-riders [82] and another between novice and advanced jockeys [86], highlighting the involvement of other core stabilizers. Greater mediolateral amplitude and velocity of the center of pressure have been measured during riding in a group of cerebral palsy participants with five years of therapeutic riding experience compared to controls, also illustrating a deficit in mediolateral trunk control due to impairment [87].…”
Section: The Relationship Between Impairment and Performancementioning
confidence: 99%
“…In the article, “Analysis of trunk muscles activity during horseback riding machine exercise in children with spastic cerebral palsy,” [ 1 ] which published in Volume 101, Issue 52 of Medicine , KyungJune Lee and HyoSun Lee have been added to the author list.…”
mentioning
confidence: 99%